2018
DOI: 10.3390/nu10091242
|View full text |Cite
|
Sign up to set email alerts
|

Foods Contributing to Macronutrient Intake of Women Living in Puerto Rico Reflect Both Traditional Puerto Rican and Western-Type Diets

Abstract: Lack of variability in dietary intake within a population makes identification of relationships between diet and disease difficult. Studies in populations with greater interindividual variation can provide important insights. The Puerto Rican diet is in transition from a traditional to a more Western-type diet, resulting in greater interindividual variability. We identified foods contributing to absolute intake and variability in the intake of macronutrients among Puerto Rican women. One hundred women, aged 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…Similar to our study, others have found consistent results for low intake of fruit and vegetables and high intake of fried foods, starches, rice, and sugar-sweetened beverages [12,13,15]. A recent study ranked the top foods contributing to total energy among women in PR as white bread/rolls/crackers, rice, plantain dishes, rice and vegetable dishes, and reduced-fat milk [15]. While the percent contribution and specific ranking varied from our study, likely due to differences in food groupings, the results were consistent in ranking refined carbohydrates, dairy, and starch as the main contributors to energy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our study, others have found consistent results for low intake of fruit and vegetables and high intake of fried foods, starches, rice, and sugar-sweetened beverages [12,13,15]. A recent study ranked the top foods contributing to total energy among women in PR as white bread/rolls/crackers, rice, plantain dishes, rice and vegetable dishes, and reduced-fat milk [15]. While the percent contribution and specific ranking varied from our study, likely due to differences in food groupings, the results were consistent in ranking refined carbohydrates, dairy, and starch as the main contributors to energy.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, others have found consistent results for low intake of fruit and vegetables and high intake of fried foods, starches, rice, and sugar-sweetened beverages [12,13,15]. A recent study ranked the top foods contributing to total energy among women in PR as white bread/rolls/crackers, rice, plantain dishes, rice and vegetable dishes, and reduced-fat milk [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The foods that were mentioned as difficult to eliminate from the diet have all been reported as frequently consumed in PR, especially sugary beverages, sweets and desserts, fats and fried foods, and white rice ( 6 , 7 , 9 , 10 ). Other populations have also expressed a high preference for white rice, a staple food in the Latino culture, over potential substitutes such as brown rice, despite a willingness to reduce its intake ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these efforts, following a healthy diet continues to be challenging, as evidenced by the low diet quality reported for most residents of the United States, with well-documented disparities for low socioeconomic and racial/ethnic minority groups (2)(3)(4). Specifically, the population of Puerto Rico (PR) has inequitable health-related behaviors, including low diet quality and poor nutritional intake (5)(6)(7)(8)(9)(10), as well as the high prevalence of multiple chronic diseases that may be prevented by following a healthy lifestyle (11). It is thus important to understand which strategies for healthy eating may be appropriate for a population, especially underserved individuals with inequitable health.…”
Section: Introductionmentioning
confidence: 99%